Analysis and trends of photo-trapping in Mexico: text mining in R - Mandujano, S. (THERYA, 2019)
This paper gathers published studies that used photo-trapping as the primary or supplementary method to obtain data on mammal and bird species in Mexico. The aim is to determine temporal trends, scientific journals, species, research groups, regions, and key topics investigated using this technology. A secondary objective of this paper was to illustrate the usefulness of text mining tools to analyze and summarize relatively large amounts of information. Papers about photo-trapping in Mexico published in specialized journals and books from 1998 to 2017 were compiled from Google Scholar and processed with various packages in R. A total of 188 papers about photo-trapping in Mexico were compiled, with 88.2 % published in 50 journals over the past seven years. The main journals were Therya, Revista Mexicana de Biodiversidad, Acta Zoologica Mexicana (New Series) and Revista de Biología Tropical. The articles identified were written by 406 co-authors, 28 of whom contributed with 32.4 % of the papers published. A total of 40 species were reported in the title and abstract of these papers; the most frequent species were Panthera onca, Leopardus pardalis, Puma concolor, Tapirus bairdii, Tayassu pecari, Odocoileus virginianus, and Cuniculus paca. Oaxaca, Campeche, Sonora, Chiapas, Guanajuato, and Puebla were the main states where studies were conducted; in particular, most of them were carried out within Biosphere Reserves. Major research topics comprised records that broaden the distribution range, estimates of relative abundance and density, analysis of activity patterns, ecological interactions between species, and use of photo-trapping data as supplementary information to elaborate inventories of species. The analysis of text mining clearly indicates a trend towards an increasing use of photo-trapping in Mexico. Felines, ungulates and various species of the order Carnivora are main subjects of study. Photo-trapping has been used to explore a number of aspects of the biology of animal species. A large number of studies have been carried out in southeastern Mexico. The use of text mining techniques is a practical approach to analyze large volumes of data.